2019
DOI: 10.24875/rmoe.m18000034
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between rebound tonometer and Tono-Pen® in relation to Goldmann applanation tonometry and the influence of central corneal thickness on these three methods

Abstract: Objective: to compare intraocular pressure (IOP) measurements from two different instruments, the rebound tonometer (Icare  ) and the Tono-Pen  XL (TP), with that from Goldmann applanation tonometer (GAT) and to determine the influence of central corneal thickness on these three instruments. Methods: 274 eyes from 137 healthy volunteers were evaluated in this cross-sectional study. All IOP measurements were made by the same examiner who was blinded to the observed result. Icare  tonometry was performed firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Over time, investigators have reported comparison studies in which TP reveal IOP greater than, equal to, and less than IOPs measured by the current gold standard GAT. [3–28]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, investigators have reported comparison studies in which TP reveal IOP greater than, equal to, and less than IOPs measured by the current gold standard GAT. [3–28]…”
Section: Introductionmentioning
confidence: 99%
“…This variability and inconsistencies in reported studies have resulted in a confused professional literature. The variability has been explained by differences in research study designs, [3] research methods applied, [4] statistical approaches used to analyze IOP measurements, [5,6] eye biomechanics, [7,8] diurnal variations of IOP, [9] body positions in which measurements were taken (sitting or supine), [10,11] age of subjects, [12–14] ethnicity of subjects, [15] central corneal thickness (CCT), [7,16–21,29] cornea shape, [22] level of training and skill of eye care professional making the measurements (ophthalmologist, technician), [23,24] subjectivity of GAT measurements, [25,26] and fundamental principles of physics underlying the differences in how IOP are measured by the TP or GAT procedure. [7,22,27,28,30]…”
Section: Introductionmentioning
confidence: 99%